Z-Contrast STEM Imaging of Long-Range Ordered Structures in Epitaxially Grown CoPt Nanoparticles. (26th June 2013) - Sato, Kazuhisa; Yanajima, Keigo; Konno, Toyohiko J.
Abstract : We report on atomic structure imaging of epitaxial L10 CoPt nanoparticles using chemically sensitive high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). Highly ordered nanoparticles formed by annealing at 973 K show single-variant structure with perpendicular c -axis orientation, while multivariant ordered domains are frequently observed for specimens annealed at 873 K. It was found that the (001) facets of the multivariant particles are terminated by Co atoms rather than by Pt, presumably due to the intermediate stage of atomic ordering. Coexistence of single-variant particles and multivariant particles in the same specimen film suggests that the interfacial energy between variant domains be small enough to form such structural domains in a nanoparticle as small as 4 nm in diameter.